A Continuing Global Threat of a Neglected Tropical Disease: Dengue - Reddy Kasarla, Rahul; Thummala, Sruthi Reddy; Kasarla, Rajeshwar Reddy (Medical Journal of Eastern Nepal, 2023)
Dengue fever is one of the most important mosquito borne neglected tropical disease of major public health concern. The disease may be asymptomatic or may give rise to undifferentiated fever, dengue fever, dengue haemorrhagic fever, or dengue shock syndrome. This review outlines the current knowledge of the dengue virus, mosquito vector, transmission, immune pathogenesis, clinical manifestations, diagnosis, and the treatment and management and prevention and control of these infections and recent advances in vaccine development.